2023
DOI: 10.1101/2023.11.06.565869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An output-null signature of inertial load in motor cortex

Eric A. Kirk,
Keenan T. Hope,
Samuel J. Sober
et al.

Abstract: Coordinated movement requires the nervous system to continuously compensate for changes in mechanical load across different contexts. For voluntary movements like reaching, the motor cortex is a critical hub that generates commands to move the limbs and counteract loads. How does cortex contribute to load compensation when rhythmic movements are clocked by a spinal pattern generator? Here, we address this question by manipulating the mass of the forelimb in unrestrained mice during locomotion. While load produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(127 reference statements)
0
0
0
Order By: Relevance
“…1e), individual interneurons' firing patterns corresponded to extensor muscle activation with varying degrees: some showed rough similarity, while others did not resemble muscle activation at all. Previous work has suggested that circular or elliptical trajectories underlying neural population activity could set a basic rhythm to support pattern generation (Kirk et al, 2023;Lindén et al, 2022;Russo et al, 2018;Saxena et al, 2022). One hypothesis is that neural populations control timing by adjusting the speed of these rotational dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1e), individual interneurons' firing patterns corresponded to extensor muscle activation with varying degrees: some showed rough similarity, while others did not resemble muscle activation at all. Previous work has suggested that circular or elliptical trajectories underlying neural population activity could set a basic rhythm to support pattern generation (Kirk et al, 2023;Lindén et al, 2022;Russo et al, 2018;Saxena et al, 2022). One hypothesis is that neural populations control timing by adjusting the speed of these rotational dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has suggested that circular or elliptical trajectories underlying neural population activity could set a basic rhythm to support pattern generation (Kirk et al, 2023; Lindén et al, 2022; Russo et al, 2018; Saxena et al, 2022). One hypothesis is that neural populations control timing by adjusting the speed of these rotational dynamics.…”
Section: Resultsmentioning
confidence: 99%